Evaluation of the Zoonotic Potential of Transmissible Mink Encephalopathy - Comoy, Emmanuel E.; Mikol, Jacqueline; Ruchoux, Marie-Madeleine; Durand, Valérie; Luccantoni-Freire, Sophie; Dehen, Capucine; Correia, Evelyne; Casalone, Cristina; Richt, Juergen A.; Greenlee, Justin J.; Torres, Juan Maria; Brown, Paul; et al. (My University, 2013)
Successful transmission of Transmissible Mink Encephalopathy (TME) to cattle supports the bovine hypothesis for the still controversial origin of TME outbreaks. Human and primate susceptibility to classical Bovine Spongiform Encephalopathy (c-BSE) and the transmissibility of L-type BSE to macaques indicate a low cattle-to-primate species barrier. We therefore evaluated the zoonotic potential of cattle-adapted TME. In less than two years, this strain induced in cynomolgus macaques a neurological disease similar to L-BSE but distinct from c-BSE. TME derived from another donor species (raccoon) induced a similar disease with even shorter incubation periods. L-BSE and cattle-adapted TME were also transmissible to transgenic mice expressing human prion protein (PrP). Secondary transmissions to transgenic mice expressing bovine PrP maintained the features of the three tested bovine strains (cattle TME, c-BSE and L-BSE) regardless of intermediate host. Thus, TME is the third animal prion strain transmissible to both macaques and humanized transgenic mice, suggesting zoonotic potentials that should be considered in the risk analysis of animal prion diseases for human health. Moreover, the similarities between TME and L-BSE are highly suggestive of a link between these strains, and therefore the possible presence of L-BSE for many decades prior to its identification in USA and Europe.
Citation: Comoy, E.E.; Mikol, J.; Ruchoux, M.-M.; Durand, V.; Luccantoni-Freire, S.; Dehen, C.; Correia, E.; Casalone, C.; Richt, J.A.; Greenlee, J.J.; Torres, J.M.; Brown, P.; Deslys, J.-P. Evaluation of the Zoonotic Potential of Transmissible Mink Encephalopathy. Pathogens 2013, 2, 520-532.
Keywords: Cattle; Primate; Prion; Raccoon; Tme; Transgenic Mice